MENINGKATKAN KEMAMPUAN SOSIAL EMOSIONAL MELALUI PEMBELAJARAN PROJECT BASED LEARNING DI RA BUNAYYA IV - Lita Anggraini; Salma Rozana (Smart Education, 2025)
Abstract: The implementation of Project Based Learning (PjBL) learning in RA Bunayya IV is expected to improve social skills in students. Social emotional skills include aspects of cooperation, interaction and following rules and instructions, which are important foundations for early childhood development. The study involved a quantitative method based on experiments, involving two groups: an experimental group that was implemented with PjBL and a control group that used conventional methods. The research subjects consisted of 30 early childhood children who were divided into two groups. The observation stage was continued with a questionnaire and ended with an interview conducted in collecting the required data. Data analysis was carried out using statistical techniques to measure the differences before and after the implementation of the method. The results of the study showed that the implementation of PjBL significantly improved and could provide recommendations for the implementation of this method in the early childhood education curriculum. Keyword: RA Bunayya IV, Early Childhood Education, Social Emotional Abstrak: Penerapan pembelajaran Project Based Learning (PjBL) di RA Bunayya IV diharapkan dapat meningkatkan kemampuan sosial pada peserta didik. Kemampuan sosial emosional meliputi aspek kerja sama, interaksi dan mengikuti aturan dan instruksi, yang merupakan fondasi penting bagi perkembangan anak usia dini. Penelitian melibatkan metode kuantitatif berdasarkan eksperimen, yang melibatkan dua kelompok: kelompok eksperimen yang diterapkan dengan PjBL dan kelompok kontrol yang menggunakan metode konvensional. Subjek penelitian terdiri dari 30 anak usia dini yang dibagi menjadi dua kelompok. Tahapan observasi dilanjutkan kuesioner, dan diakhiri wawancara dilakukan dalam pengumpulan data yang dibutuhkan. Analisis data dilakukan dengan teknik statistik untuk mengukur perbedaan sebelum dan sesudah penerapan metode. Hasil penelitian menunjukkan bahwa penerapan PjBL secara signifikan meningkatkan dapat memberikan rekomendasi untuk implementasi metode ini dalam kurikulum pendidikan anak usia dini. Kata kunci: RA Bunayya IV, Pendiikan Anak Usia Dini, Sosial Emosional